2023
DOI: 10.3390/jof9020233
|View full text |Cite
|
Sign up to set email alerts
|

Plant Growth Promoting Bacteria and Arbuscular Mycorrhizae Improve the Growth of Persea americana var. Zutano under Salt Stress Conditions

Abstract: In Peru, almost 50% of the national agricultural products come from the coast, highlighting the production of avocado. Much of this area has saline soils. Beneficial microorganisms can favorably contribute to mitigating the effect of salinity on crops. Two trials were carried out with var. Zutano to evaluate the role of native rhizobacteria and two Glomeromycota fungi, one from a fallow (GFI) and the other from a saline soil (GWI), in mitigating salinity in avocado: (i) the effect of plant growth promoting rhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…Karlidag et al (2013) discovered that PGPR inoculation enhanced the Mg 2+ , Ca 2+ , K, and P content of strawberry leaf and root in comparison to non-inoculated plants in salinity conditions. Soloŕzano-Acosta et al (2023) found that Rhizobacteria Pseudomonas plecoglossicida, and Bacillus subtilis contributed to the accumulation of potassium in the leaves, compared to the uninoculated control under salt stress condition.…”
Section: Discussionmentioning
confidence: 90%
“…Karlidag et al (2013) discovered that PGPR inoculation enhanced the Mg 2+ , Ca 2+ , K, and P content of strawberry leaf and root in comparison to non-inoculated plants in salinity conditions. Soloŕzano-Acosta et al (2023) found that Rhizobacteria Pseudomonas plecoglossicida, and Bacillus subtilis contributed to the accumulation of potassium in the leaves, compared to the uninoculated control under salt stress condition.…”
Section: Discussionmentioning
confidence: 90%